Peripheral neighbourhoods and the Ciompi revolt (Florence, 1378). An interpretive hypothesis (Studi di storia medioevale e di diplomatica - Nuova Serie, 2023)
Over the last few decades, the concept of spatial turn that has influenced various disciplines has taught us – or, rather, emphatically reaffirmed – that space is fundamental to understanding many economic, social, cultural and political dynamics. The article takes its cue from this assumption and reconsiders a much (and very well-) studied episode, the Ciompi riot by placing the spaces of the riot and the rioters at the heart of the analysis. It tries to demonstrate, also by resorting to scholarly literature in anthropology and sociology published over the last decades, how giving back importance to the  dimension of space can contribute to tackling some very relevant questions for understanding the events that unraveled during the summer of 1378: the construction of a shared social identity, the definition of a ‘class’ solidarity, the elaboration of a discourse alternative to that of the elite, capable of sustaining the mobilization of a similar scale and with such ambitious objectives.
Keywords: Ciompi; revolt; free spaces; peripheries; contrade